EVALUATION OF THE STRESSED-STRAIN CONDITION OF THE ROOF TRUSSES OF ONE-STOREYED INDUSTRIAL BUILDING IN THE END BRACE BLOCKS TAKING INTO ACCOUNT THE WIND PRESSURE AT THE FLANK OF THE BUILDING (Collection of scientific works «Modern structures of metal and wood», 2020)
In the article, the authors investigate the effect of the wind load at the frank of the building  on  the  stress-strain  state  of  the  roof  trusses  in  the  end  brace  blocks.  Traditionally,  to perceive  the  wind  pressure  to  the  frank  of  the  building,  in  the  lower  zones  of  the  roof  trusses, horizontal joint trusses were arranged on the half-timbered columns by means of sheet hinges. The belts of these brace trusses were the lower belts of the roof trusses themselves, and the grid was designed additionally. Further, the support reactions of the horizontal brace trusses from the wind load, through braces in the plane of the columns, were transferred to the foundation. However, the question that the lower belt of the roof truss performs the functions of a belt and a  brace  truss  and  that  the  forces  from  the  vertical  load  are  combined  in  it,  was  not  considered. Therefore,  it  is  necessary  to  evaluate  the  effect  of  wind  pressure  at  the  flank  of  an  industrial building on the stress-strain state of brace trusses in end brace blocks. The  authors  are  developing  a  method  for the  quantitative  assessment of  the  effect of  wind pressure on the flank of industrial buildings on the stress-strain state of roof trusses in end brace blocks. The  efforts  in  brace  trusses  are  determined  in  the  lower  belts  of  the  roof  trusses  from concentrated single  forces of wind pressure to the  flake of the  industrial  building, applied at the nodes of the lower belt of the roof trusses - at the level of the sheet hinges on the half-timbered columns at the ends of the building. The authors consider the geometric patterns of brace trusses along the lower belts of the roof trusses with the efforts in their elements from a unit nodal load of wind pressure to the flake of an industrial building for typical spans of 18, 24, 30, and 36 m. It is easy to evaluate the effect of wind pressure on the stress-strain state of the roof trusses in the coupling end blocks, having obtained unit efforts in the elements of brace trusses for any typical spans. For example, an  industrial  building with a span of 36  m and a 6  m step of bent located in Kramatorsk is considered. For a brace truss with a span of 36 m, the maximum tensile force in the belt from a single horizontal nodal load and the actual one were found. It should be noted that the function of the belt of the brace truss is performed by the lower belt of the roof truss, the  load  bearing capacity of which, taking  into account the calculated ultimate load, was 3%. But the effort in the lower belt of the roof trusses in the end brace block increases due to wind pressure at the flank of the building. The combination of two functions in the element of the lower belt leads to a change in the stress state - overwork in the lower belt was 27%. To  the  roof  trusses  of  the  industrial  buildings  in  end  brace  blocks,  a  special  approach  is needed in assessing the stress-strain state in them. The  proposed  methodology  makes  it  possible  to assess  the  stress-strain  state of  the  typical spans roof trusses of industrial buildings in end brace blocks.